The Effect of Pencak Silat Extracurricular Activities in Student Character Building: A Literature Review as a Theoretical Approach - Jefrio Demitrimus Nubatonis; Dwi Manna Nasmi Dzakiyyah; Muhamad Husein; Zsolt Németh; Procopio B. Dafun JR (Khatulistwa Education Center, 2025)
Background Extracurricular activities in schools play an important role in student character building, one of which is pencak silat. This study aims to analyze the influence of pencak silat extracurricular activities on student character building through a literature review approach. Objectives This study reveals that pencak silat not only develops physical abilities, but also values of discipline, responsibility, and respect for others. Through literature analysis, this study concludes that pencak silat can be an effective medium in student character building. Methods Research method This research uses a literature review approach by analyzing various secondary sources such as relevant journals, books, and articles. The analysis process involves identifying, evaluating, and synthesizing findings related to pencak silat and character building. Results The results of this study show that pencak silat extracurricular activities contribute significantly to student character building. The values taught in pencak silat include discipline, responsibility, cooperation, and respect, which are important for students' character development. Therefore, schools need to support this activity as an integral part of character education. Conclusion Based on a literature review, extracurricular pencak silat activities contribute significantly to student character development. The values taught in pencak silat include discipline, responsibility, cooperation, and respect, which are essential for student character development. Therefore, schools need to support these activities as an integral part of character education.